Investigations into fibre laser cutting - Hashemzadeh, Majid (2014)
Fibre laser cutting of mild steel using oxygen and nitrogen is widely used in industries throughout the world. An IPG YLR-2000 Ytterbium fibre machine with a maximum power of 2 kW and a wavelength of 1.06 µm is used throughout this research. The effects of oxygen and nitrogen as assist gases on the feature of laser cutting process are different in terms of kerf width, surface roughness, heat affected zone and striation pattern. The kerf width in oxygen laser cutting is wider than that for nitrogen. The striation pattern on oxygen cut edge is smoother than that for the nitrogen cut edge. When using oxygen, the cut edge is covered by a fragile oxide layer while this feature is not seen on the nitrogen cut edge. After laser cutting with oxygen, the cut edge is dross free whilst nitrogen cut edge is drossy.